Methodological aspects of economic behavior of enterprises simulation - Karachyna, N. P.; Lazarchuk, O. V.; Hanziienko, N. I. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Methodological principles of the category “Economic behavior of an enterprise” as one of the key category of explanation of enterprises functioning are formulated. Description of the model of enterprise’s economic behavior was performed; the economic and mathematical description of efficiency of the model of economic behavior for formulation of more efficient policy and strategy of an enterprise is suggested.